PP.40.16: CAROTID INTIMA-MEDIA AND EXTRA-MEDIA THICKENING IN ELDERLY SUBJECTS WITH RESISTANT HYPERTENSION. (June 2015) - D'Amico, F.; Grasso, R.
Abstract : Objective: The carotid intima-media thickness is an early marker for arterial vascular damage, therefore it can produce atherosclerotic harm. This study assessed the relationship between the carotid intima-media thickness, the extra-media thickness and cardiovascular risk factors in elderly subjects affected by hypertension. Design and method: 35 elderly subjects with Resistant Hypertension (RH) (aged 75.03+ 8) were enrolled and classified following the guidelines; 38 had essential hypertension (aged 77.07+ 7), controlled (values <140/90) through monotherapy or combined therapy. The design of this study included: 1) clinical measurement of blood pressure; 2) blood tests; 3) epiaortic colordoppler. Controlled hypertension resulted in BP values <140/90 and 130/80 for patients affected by diabetes mellitus. Data on age, body mass, hypertension history, smoking, glycemia, cholesterol, tryglicerids, creatinine, were similar in both groups. Results: Clinic hypertension was higher in patients with RH compared to CH subjects (157+16/96+7 vs 128 +7/82+5 mmHg, p < 0.01). RH patients have been studied through the ABPM for a 24-hour-time to leave out a possible RH (values >140/90 mmHg and MBP 24-hour < 125/79 mmHg). We measured the thickness of carotid intima-media (IMT): 2.1 + 1.3 mm in group CH, 2.6 + 1.4 mm in group R. We also measured the extra-media wall thickness. Hypertensive subjects showed an increasing IMT and a higher number of carotid plaques with a higher rate of EMT compared to patients with controlled hypertension. In group RH we also detected several factors of cardiovascular risk: obesity BMI> 30 kg /m m2 (31.2% p = 0.06), diabetes mellitus (18.4%, p < 0.001), hypercholesterolemia >200 mg (46.4%, p < 0.005), smoking (14.2%, p < 0.005), microalbuminuria (1.7%, p < 0.005), history of coronary disease (47, 5%, p < 0.001), history of stroke (16, 3%, p < 0.001). In the same subjects we detected that carotid extra-media thickness was mostly associated to age (p = 0.030) and HDL cholesterol (p = 0.010). Conclusions: Subjects affected by RH showed an increased carotid intima-media thickness, extra-media thickness, a higher number of carotid plaques and a higher cardiovascular risk compared to subjects with controlled hypertension.